The phenomenology of everyday life - Pollio, Howard R. (Cambridge University Press, 1997)
The Phenomenology of Everyday Life presents results from a rigorous qualitative approach to the psychological study of everyday human activities and experiences. This book does not replace scientific observation with humanistic analysis, but provides an additional perspective on significant human questions. The qualitative approach this book employs is grounded in the philosophical traditions of existentialism and phenomenology, which use dialogue as their major method of inquiry. These traditions are especially well adapted to encompass and describe human events and activities. In addition, such events can be properly investigated only on the basis of a method sensitive enough to articulate the nuances of human experience and reflection. In this latter regard, it is important to note that insights deriving from literature and the humanities are equally revealing of the human world as those from experimental psychology, biology or medicine
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Phenomenological psychology; Phänomenologie; Phänomenologische Psychologie; Alltag